2020
DOI: 10.1038/s41598-020-58687-z
|View full text |Cite
|
Sign up to set email alerts
|

The upper cervical spinal cord in ALS assessed by cross-sectional and longitudinal 3T MRI

Abstract: the upper cervical spinal cord is measured in a large longitudinal amyotrophic lateral sclerosis (ALS) cohort to evaluate its role as a biomarker. Specifically, the cervical spinal cord´s cross-sectional area (CSA) in plane of the segments C1-C3 was measured semi-automatically with T1-weighted 3T MRI sequences in 158 ALS patients and 86 controls. Six-month longitudinal follow-up MRI scans were analyzed in 103 patients. Compared to controls, in ALS there was a significant mean spinal cord atrophy (63.8 mm² vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 36 publications
7
16
0
Order By: Relevance
“…Quantitative MRI (qMRI) of the cervical SC has been widely used to investigate cord pathology in several neurodegenerative disorders such as MS ( 21 , 22 ) and ALS ( 23 , 24 ). Through the acquisition of images with high contrast between white matter (WM) and gray matter (GM), SC MRI enables tissue segmentation and measurement of the cross-sectional area (CSA) of the SC, total GM, and ventral horns (VHs), thus making it possible to quantify total SC and GM atrophy ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative MRI (qMRI) of the cervical SC has been widely used to investigate cord pathology in several neurodegenerative disorders such as MS ( 21 , 22 ) and ALS ( 23 , 24 ). Through the acquisition of images with high contrast between white matter (WM) and gray matter (GM), SC MRI enables tissue segmentation and measurement of the cross-sectional area (CSA) of the SC, total GM, and ventral horns (VHs), thus making it possible to quantify total SC and GM atrophy ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, there is sparse evidence about regional distribution patterns and in vivo changes of atrophy and other mechanistic alterations affecting the spinal cord in human ALS. Two recent 3T studies reported cervical cord atrophy in ALS participants, but these studies evaluated limited portions of the cervical spinal cord ( Grolez et al, 2018 , Wimmer et al, 2020 ). The Grolez et al study ( Grolez et al, 2018 ) evaluated a short segment of the cord between vertebral levels C3 and C5 in 40 ALS participants and observed correlations of spinal cord volume reduction with slow vital capacity decline from baseline.…”
Section: Discussionmentioning
confidence: 99%
“…The Grolez et al study ( Grolez et al, 2018 ) evaluated a short segment of the cord between vertebral levels C3 and C5 in 40 ALS participants and observed correlations of spinal cord volume reduction with slow vital capacity decline from baseline. Another recent multi-center study ( ) similarly examined only the rostral cervical cord (C1–C3) and observed a 5% decrease in cord CSA at these levels in ALS compared to HCs at baseline (60.8 mm 2 vs. 63.8 mm 2 ) ( Wimmer et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Differing patterns in sporadic and SOD1 MND/ALS patients have also been reported, with intracranial corticospinal tract FA reduction and cervical cord atrophy predominating, respectively [50]. Longitudinal studies focussed on either brain or cervical cord in isolation have shown progression of intracranial grey [20] and white matter tissue damage [34,[51][52][53] in some, but not all [17,54], studies, with only modest cervical cord atrophy evident even in quite large cohorts (mean 0.8 mm 2 over 6 months in 103 patients, not reaching statistical significance) [40]. Results of studies of asymptomatic gene carriers, which represent an ideal model of the earliest stages of MND/ALS, have reported early detectable changes both at cortical [8] and cord levels [50,55].…”
Section: Discussionmentioning
confidence: 99%
“…MRI is often performed routinely at diagnosis of MND/ ALS primarily to exclude mimics, but also provides established group-level markers of tissue damage. Primary motor cortical thinning on T1-weighted MRI [17][18][19][20][21][22][23][24], decreased fractional anisotropy (FA) within corticospinal tracts on diffusion tensor imaging [14,[25][26][27][28][29][30][31][32][33][34][35] and reduced crosssectional area of the cervical spinal cord [36][37][38][39][40] have been consistently reported. The aim of this study was to determine whether analysis of these metrics in a common domain could demonstrate group-level gradients of tissue damage to support either a dying-forward or dying-back hypothesis.…”
Section: Introductionmentioning
confidence: 99%